2003
DOI: 10.1046/j.1470-6431.2003.00308_43.x
|View full text |Cite
|
Sign up to set email alerts
|

The attitudes and nutritional knowledge of 11–12 years olds in Merseyside and Northern Ireland

Abstract: School is a major area for providing young people with nutritional knowledge and skills. In Northern Ireland home economics is taught to 11–12 years olds (CCEA,1998). The 1988 Education Reform Act introduced the national curriculum and home economics as a subject was effectively abolished in English schools. Key stage 3 pupils in England are taught nutrition in Science, Design and Technology and in the cross curricular theme of health education (SCAA, 1996). The aim of the study was to compare the attitudes an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2009
2009
2011
2011

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 0 publications
0
4
0
1
Order By: Relevance
“…They seek enjoyment from food and are health conscious (Sloan, 2005). Among youth, awareness of the need to adopt a healthier lifestyle seems to be growing (McCullough et al, 2003). However, when faced with time constraints, young people opt for convenience and for easy-to-prepare foods (Glanz et al, 1998) to the detriment of nutrition (National Institute of Nutrition, 2002).…”
Section: Eating Behavior and Gendermentioning
confidence: 99%
See 2 more Smart Citations
“…They seek enjoyment from food and are health conscious (Sloan, 2005). Among youth, awareness of the need to adopt a healthier lifestyle seems to be growing (McCullough et al, 2003). However, when faced with time constraints, young people opt for convenience and for easy-to-prepare foods (Glanz et al, 1998) to the detriment of nutrition (National Institute of Nutrition, 2002).…”
Section: Eating Behavior and Gendermentioning
confidence: 99%
“…However, when faced with time constraints, young people opt for convenience and for easy-to-prepare foods (Glanz et al, 1998) to the detriment of nutrition (National Institute of Nutrition, 2002). Studies have shown that convenience foods appeal to university students because they compensate for their poor cooking skills, allowing them to spend less time preparing meals, which enables them to proceed more quickly to another activity (Marquis, 2005;McCullough et al, 2003).…”
Section: Eating Behavior and Gendermentioning
confidence: 99%
See 1 more Smart Citation
“…Food patterns differ in accordance with the knowledge of food and health. The more people know about the foodstuff they eat, the higher is the probability that they make healthier food choices (Ohr et al, 2001;McCullough et al, 2003). Schwartz et al (1998) shows that the importance of information retrieval, as well as the scope of information gained and the variety of individual healthoriented activities, depend on the social status.…”
Section: Food Knowledgementioning
confidence: 99%
“…and Cohen, 1995, Ahlgren et al, 2004, Scholderer and Grunert, 2005 (Buckley et al, 2005), η αντίληψη για την υγιεινή των τροφίµων και η ανησυχία σχετικά µε την υγεί (Darian nd Cohe , 1995, McCullough et al, 2003, Akbay et al, 2007, η αντίληψη στενότητας χρόνου (Darian στενότητας χρήµατος (Scholderer and Grunert, 2005), η στάση ως προς την τιµή του φαγητού (Akbay et al, 2007), η στάση ως προς τον χρόνο (Davies and Madran, 1997), η ευχαρίστηση στη µαγειρική (Madill- Marshall et al, 1995, Davies andMadran, 1997), η ικανοποίηση από τη ζωή και το αίσθηµα στρες (Madill- Marshall et al, 1995), η αντίληψη της εθνικής ταυτότητας (Laroche et al, 1998) αλλά και οι περιστασιακοί καθοριστικοί παράγοντες (situational determinants) (Verlegh and Candel, 1999, Ahlgren et al, 2005, Schöder and McEachern, 2005 , Tzimitra-Kalogianni, 1996. Η κατανόηση των στάσεων επιτρέπει στους παραγω στις ανάγκες και τις επιθυµίες των καταναλωτών και να τα προωθήσουν αποδοτικά.…”
Section: στρατηγικές οικονοµίας χρόνουunclassified